Complete chloroplast genome of Ulva compressa (Ulvales: Ulvaceae) - Xia, Lihua (Mitochondrial DNA B Resour, 2021)
Ulva compressa is one of the causal green macroalgae in many countries. In this study, complete chloroplast genome sequence of U. compressa was reported, and the total length of this species was 94,226 bp (GenBank accession number MT916929). The overall base composition of chloroplast genome was A (37.2%), T (37.0%), C (12.7%) and G (13.1%), and the percentage of A + T (74.2%) was higher than C + G (25.8%). U. compressa chloroplast genome encoded 90 genes, including 63 protein-coding genes, 23 transfer RNAs genes, and 4 ribosomal RNAs genes. The maximum likelihood phylogenetic analysis showed that U. compressa is the closest sister species of U. linza. This study will be helpful to understand the genetic diversity of Ulva species.